Estimation du flux nocturne, diurne et cumulé du CO2 dans quelques occupations du sol au sein du jardin zoologique de Kisangani /RDC. - Esther, Ndongo Yekola; Angbonga Basya Albert; Monde Te-kazangba Godefroid; Meniko Tohulu Pitchou (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2019)
The major concerns raised in this study were to know, on the one hand, the variations in space and time of carbon flux released by the soil as well as climatic factors (humidity and soil temperature) which explain better these CO2 variations across the three types of soil occupations at the occurrence, the under-forested soil, the young fallow soil and the bare soil. On the other hand, it was necessary to measure the variations of the nocturnal and diurnal fluxes of carbon dioxide released by the soil through the three types of occupations mentioned above and to reveal their variations between these occupations of the soil. After the analyzes, it follows that: Soil carbon outflows vary in space and not in time and are positively correlated with soil moisture between different land uses; The soil carbon fluxes released during the day remained higher than those released at night due to the large variation in temperature and soil moisture content; Soil carbon fluxes released by forested soil remained well above those released by young fallow soil, and those above those released by bare soil, following a large root biomass and litter soil under the planting species in the tropical environment. The CO2 released under forest, although higher than that released by the soil under young fallow and on bare ground, will be quickly offset by the process of carbon sequestration carried out by the existing trees. Key words: soil respiration, mixed forests, young fallow, bare soil, CO2